EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL THINK TALK WRITE (TTW) DAN MISSOURI MATHEMATICS PROJECT (MMP) DITINJAU DARI GAYA BELAJAR SISWA KELAS VII SMP NEGERI DI KABUPATEN PACITAN TAHUN AJARAN 2012/2013 - Sutarman, Sutarman; Mardiyana, Mardiyana; Triyanto, Triyanto (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of the research were to find out: (1) which one was improving better the students mathematics learning achievement, Think-Talk-Write (TTW) or Missouri Mathematics Project (MMP) and Conventional Learning model, (2) which one was providing better to mathematics learning achievement, the students who used visual, auditory, or kinesthetic learning style (3) who the students were provided to be better in mathematics learning achievement by applied the TTW, MMP, and Conventional model on each learning style. The research method used was a quasi-experimental research with 3x3 factorial design. The population of the research were the students of junior high schools in Pacitan regency in the school in year of 2012/2013. The sampling technique used was stratified cluster random sampling. The were 275 students who were divided into three groups. The groups devided into the experiment I, experiment II, and control class. Experiment I was consisted of 92 students, experiment II was consisted of 92 students, and control class was consisted of 91 students. The instruments used to collect the data were the students learning styles questionnaire, the students achievement in mathematics and documentation. The technique of data used was an unbalanced two ways analysis of variance. The results of the reseach were as follows: (1) the mathematics learning achievement to the students who were given the TTW learning model were as same as to the students were given the MMP learning model, but they were better than the students, learning achievement who were taught by the conventional learning model, The students learning achievement in the MMP learning model were as same as to the students learning achievement in the conventional learning model. (2) the mathematics learning achievement of the students by visual learning style were better than the students learning achievment by auditory or kinesthetic learning style, while the students by auditory learning style had their learning achievement as same as with the students by kinesthetic learning style. (3) the mathematics learning achievement to the students on each learning style, students were given the TTW learning model had shown the same learning achievement to students were given the MMP learning model, but they were better achievements when compared with student who were taught the conventional learning model, while the students who were given the MMP learning model has achievement as well as student who were given the conventional learning model.Keywords:     TTW learning model, MMP learning model, conventional learning model, learning style, mathematics learning achievement.